Dilema Dalam Transformasi Desa Ke Nagari : Studi Kasus di Kenagarian IV Koto Palembayan, Provinsi Sumatera Barat - Budi Astuti, Nuraini; M. Kolopaking, Lala (Sodality: Jurnal Sosiologi Pedesaan, 2009)
The implementation of local autonomy regime gives an interesting socio-political explanation of how is the local genuine governance system, the so-called nagari, to operate in West Sumatera. Based on Law No. 22/1999 as amended by Law No. 32/2004, the Regional Government of West Sumatera introduced Regional Law No. 9/2000 as legal foundation to regulate the implementation of nagari in the region. The study, was conducted in Nagari IV Koto Palembayan, District of Agam, Province of West Sumatera. It was intended to 1) describe and analyze the implication of structural change from nagari to desa and its return to nagari system, 2) analyze potential conflicts that occur in the transformation from desa to nagari. The study used qualitative approach, in which data and information were mostly collected by in-depth interviews supported by observation, study of literature and documents. It was found that 1) such intervention brought about widely social change at local level, 2) the transformation from desa to nagari stimulated some potential conflicts at local level. It is realized that it is uneasy for the government to synergize modern and traditional institution of governance in a single system. In case, the control of such a complicated system is very poor, then the implementation of nagari system is substantially hindered.